Comparative Analysis of Protein Glycosylation Pathways in Humans and the Fungal Pathogen Candida albicans - Iván Martínez-Duncker; Diana F. Díaz-Jímenez; Héctor M. Mora-Montes (International Journal of Microbiology)
Protein glycosylation pathways are present in all kingdoms of life and are metabolic pathways found in all the life kingdoms. Despite sharing commonalities in their synthesis, glycans attached to glycoproteins have species-specific structures generated by the presence of different sets of enzymes and acceptor substrates in each organism. In this review, we present a comparative analysis of the main glycosylation pathways shared by humans and the fungal pathogen Candida albicans: N-linked glycosylation, O-linked mannosylation and glycosylphosphatidylinositol-anchorage. The knowledge of similarities and divergences between these metabolic pathways could help find new pharmacological targets for C. albicans infection.